Comparison of sensory recovery between random pattern flap and axial pattern flap in finger defect reconstruction - Tien Duc Nguyen (Archives of Plastic Surgery)
Background: This study aimed to investigate the association between the use of different flaps, including random- and axial-pattern flaps, and sensory recovery following finger soft tissue reconstruction using local pedicle flaps. Methods: A longitudinal study was conducted on 115 patients with 130 finger soft tissue defects treated with local pedicle flaps between December 2016 and December 2020. Assessments were made at early postsurgery (119 flaps), three months postsurgery (110 soft tissue defects), and six months postsurgery (94 soft tissue defects). Sensory recovery outcomes were compared between soft tissue defects reconstructed using random- and axial-pattern flaps. Results: In the early postsurgery period, there was a significantly higher prevalence of a static sense of two-point discrimination (s2PD) ≤6 mm among fingers with random-pattern flaps (96.2%) than among fingers with axial-pattern flaps (64.5%). The probability of s2PD ≤ 6 mm at the donor and recipient sites with the direct flap was 75.5% and 25.5%, respectively, which was significantly higher than that with the reversed flap. After six months, there was a significant difference in sensory recovery compared to that at three months postsurgery, but not between different flap types. Conclusions: Sensory recovery after reconstruction was observed with all flap types, and better sensory recovery can be achieved in a shorter time postsurgery using random-pattern flaps.